Unveiling the hidden arsenal: new insights into Proteus mirabilis virulence in UTIs - Yang, Aoyu; Tian, Yuchong; Li, Xiancheng (Frontiers in Cellular and Infection Microbiology, 2024)
Proteus mirabilis is a Gram-negative bacterium commonly found in urinary tract infections (UTIs) and catheter-associated urinary tract infections (CAUTIs). The pathogenic mechanisms of Proteus mirabilis are complex and diverse, involving various virulence factors, including fimbriae, flagella, urease, polyphosphate kinase, lipopolysaccharides, cyclic AMP receptor protein, Sigma factor RpoE, and RNA chaperone protein Hfq. These factors play crucial roles in bacterial colonization, invasion, evasion of host immune responses, biofilm formation, and urinary stone formation. This paper is the first to comprehensively describe the hydrogenase system, autotransporter proteins, molybdate-binding protein ModA, and two-component systems as virulence factors in Proteus mirabilis, providing new insights into its pathogenic mechanisms in urinary tract infections. This review explores the mechanisms of biofilm formation by Proteus mirabilis and the various virulence factors involved in UTIs, revealing many newly discovered virulence factors from recent studies. These findings may offer new targets for clinical treatment of UTIs and vaccine development, highlighting the importance of understanding these virulence factors.